Effect of oral progesterone and caffeine at the end of gestation on farrowing duration and piglet growth and survival. (4th December 2017) - van Wettere, W. H. E. J.; Toplis, P.; Miller, H. M.
Abstract : The profitability of pig production is constrained by high incidences of peri-parturient and pre-weaning piglet mortality. Supplementing sows with either progesterone or caffeine during the last week of gestation can reduce stillbirths and improve piglet performance. However, the consequences of combining these two substances has not been investigated. The aim of the current study was to determine the effect of oral supplementation of sows with progesterone (regumate) and caffeine at the end of gestation on the timing and progression of farrowing, as well as piglet survival and growth to weaning. From days 111 to 113 of gestation, 20 Large White pregnant sows (parity 3.0±0.45) received 5 ml of Regumate Porcine (0.4 w/v oral solution; MSD Animal Health) daily on top of their morning ration. Sows were stratified according to parity and predicted farrowing date, and allocated at random to receive a diet supplemented with either 0 g caffeine/kg diet (CONT) or 2.4 g of caffeine/kg diet (CAFF) from day 113 of gestation until parturition ( n =10 sows/treatment). Treatment did not affect total litter size; however, CONT sows gave birth to more live and fewer dead piglets compared with CAFF sows; 14.5±0.73 v . 11.7±1.03 and 0.7±0.20 v . 3.2±0.77; P <0.05). Mean, minimum and maximum piglet birthweight were unaffected by treatment. Compared with the control, caffeine increased the proportion of piglets with a birthweight <1 kg (0.16±0.05 v . 0.05±0.02; P =0.072) and decreased the proportion of live born piglets surviving to day 5 postpartum (0.77±0.06 v . 0.90±0.02; P <0.05) and to weaning (0.74±0.06 v . 0.90±0.02; P <0.05). Overall, the current data provided the first evidence that caffeine supplementation of sows receiving progesterone to prevent premature farrowing impaired piglet survival during, and shortly after parturition. This negative outcome may be linked to extended farrowing durations and an increase in the proportion of very light piglets at birth. These data provide compelling, albeit preliminary, evidence that caffeine and progesterone should not be used together at the end of gestation.